SARM1: a key multifaceted component in immunoregulation, inflammation and neurodegeneration - Oliveira, Samuel dos Santos; Honório da Silva, João Vinícius; Vieira, Raquel de Souza; Moreira, Luís Felipe Serra; Bandeira, Pedro Henrique Araújo; Ramos, Beatriz Leocata; Silva, Marco Antônio Ataíde; Câmara, Niels Olsen Saraiva (Frontiers in Immunology, 2025)
The downstream signaling pathways of TLR activation involve a family of adaptor proteins, including MYD88, TIRAP, TRIF, TRAM, and SARM1. The first four proteins stimulate inflammatory and antiviral responses, playing crucial roles in innate immunity against various pathogens. In contrast, SARM1 promotes immunity to microorganisms in invertebrate animals independently of TLRs, and negatively regulates inflammatory responses in metazoan organisms. SARM1 inhibits TRIF, reduces the activation of various inflammasomes, and induces mitochondrial damage and cell death to eliminate hyperactivated cells. This regulation is essential to ensure timely control of immune responses and to prevent excessive inflammation. Recently, it was discovered that SARM1 can hydrolyze NAD, a critical component of cellular metabolism. The reduction of NAD levels by SARM1 is linked to the progression of Wallerian degeneration following neuronal injury and may also play a role in the immunoregulation of lymphoid and myeloid cells. Since SARM1 can be pharmacologically modulated, it presents promising opportunities for developing treatments for inflammatory and neurodegenerative diseases.